Can We Talk through a Robot As if Face-to-Face? Long-Term Fieldwork Using Teleoperated Robot for Seniors with Alzheimer's Disease - Kuwamura, Kaiko; Nishio, Shuichi; Sato, Shinichi (Frontiers in Psychology, 2016)
This work presents a case study on fieldwork in a group home for the elderly with dementia using a teleoperated robot called Telenoid. We compared Telenoid-mediated and face-to-face conditions with three residents with Alzheimer's disease (AD). The result indicates that two of the three residents with moderate AD showed a positive reaction to Telenoid. Both became less nervous while communicating with Telenoid from the time they were first introduced to it. Moreover, they started to use more body gestures in the face-to-face condition and more physical interactions in the Telenoid-mediated condition. In this work, we present all the results and discuss the possibilities of using Telenoid as a tool to provide opportunities for seniors to communicate over the long term.